Strata-bound pyritic copper mineralization on a fore-arc setting in northwestern India: a Proterozoic Besshi-type deposit - A. D. Mukherjee; H. N. Bhattacharya (The Institute of Materials, Minerals and Mining, 1905)
Middle Proterozoic sulphide ore mineralisation occurs in isolated blocks of the NE-SW trending Delhi fold belt composed of Delhi Supergroup rocks. The Ajari-Basantgarh-Pipela belt forms part of the longest, widest and westernmost tectonic unit of the Delhi fold belt and consists of amphibolites, metapelites, quartzites and carbonates. The metapelite lenses and associated amphibolites host pyritic copper mineralisation. Mineralisation takes the form of sheet-like bodies consisting of ore lenses of various sizes interlayered with host or associated rocks. Massive, banded and disseminated varieties of ore are found. Pyrite is dominant with subordinate chalcopyrite and sphalerite. Pyrrhotite, galena, cubanite, mackinawite, marcasite and freibergite constitute the minor minerals. The characteristic features of the ores suggest a possible correlation with Besshi-type deposits, and the closely associated amphibolites are interpreted as low-K tholeiites of a fore-arc setting